Review of seasonal polyphenism in the Symphyta (Hymenoptera), exemplified by Pristiphora leucopus (Hellén, 1948) (Tenthredinidae) - Grearson, K. John; Liston, Andrew D. (Zootaxa, 2012)
Morphological differences between the adults of overwintering and non-overwintering generations of the sawfly Pristiphora leucopus (Nematinae) are described and illustrated, as well as characters that distinguish P. leucopus from the closely similar P. armata. In the basal hymenopteran lineages (‘Symphyta’), seasonal polyphenism is so far only definitely recorded in the Sterictiphorinae (Argidae) and Nematinae (Tenthredinidae) of the Tenthredinoidea. Within the Nematinae, seasonal polyphenism had previously only been described in Nematus bergmanni. Seasonal polyphenism in the basal hymenopteran lineages is reviewed, and the potential pitfall that the existence of seasonal morphs represents for taxonomists working on ‘Symphyta’ is highlighted. Voltinism patterns in the basal hymenopteran lineages are also reviewed, to indicate the likelihood of further undetected examples of seasonal polyphenism in the families and subfamilies. With rare exceptions, multivoltinism occurs mainly in the Tenthredinoidea and is most frequent in the Argidae and Tenthredinidae (particularly Allantinae, Blennocampinae and Nematinae).